Severe asthma phenotypes in patients controlled with omalizumab: A real-world study. (November 2019) - Campo, Paloma; Soto Campos, Gregorio; Aparicio, Marina Blanco; Jorge, Ana Moreira; González Expósito, Héctor Manuel; Quirce, Santiago; Dávila, Ignacio
Abstract: Background: The appropriate identification of asthma phenotypes of responders to omalizumab would optimize the selection of treatment. Objective: To describe the most frequent clinical phenotypes in patients with severe asthma responding to omalizumab and their clinical and pulmonary function improvement. Methods: This was an observational, retrospective, multicenter study. Adult patients with severe asthma, who achieved good control after the first year of treatment with omalizumab were included. Omalizumab was prescribed according to clinical routine practice. Responders were assigned to one pre-established phenotype based on the most predominant one before they had started treatment with omalizumab, all according to the physician's criteria. Data about asthma symptoms, number of non-severe asthma exacerbations, medication intake (inhaled and oral corticosteroids and rescue medication), lung function, high fractional exhaled nitric oxide (FeNO) and peripheral eosinophils counts were recorded. Results: Among the 345 patients included, the main phenotypes were severe asthma with frequent exacerbations (29.9%), early-onset allergic asthma (23.8%), severe steroid-dependent asthma (18.8%), and severe eosinophilic asthma (13.6%). Clinical and respiratory changes observed after first year of treatment with omalizumab included: reduction in asthma symptoms, reduction in the use and dose of corticosteroids and need for rescue therapy, improvement of pulmonary function, reduction in the number of episodes of non-severe asthma exacerbations regardless of the duration of severe disease since the diagnosis. Increased blood levels of peripheral eosinophils and high FeNO levels were found at baseline. Conclusion: Several heterogeneous severe asthma phenotypes were observed as good responders to omalizumab. Highlights: What is already known about this topic? Phenotypic heterogeneity exists in severe asthma patients. However, these phenotypes are not yet fully characterized. What does this article add to our knowledge? This article adds real-world data regarding common clinical phenotypes responding to omalizumab, after one year of treatment. How does this study impact current management guidelines? This data could help physicians to identify the right candidates who respond to omalizumab treatment.